2020
DOI: 10.1111/jcmm.16060
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: SLC1A3 promotes gastric cancer progression via the PI3K/AKT signalling pathway

Abstract: Gastric cancer is one of the most common cancers and is a leading cause of mortality worldwide. 1,2 The National Central Cancer Registry of China (NCCR) estimated that there were 679 000 new cases, and more than 498 000 deaths from this disease in China in 2015. 3 There were an estimated 27 000 new cases and 11 140 deaths in the United States in 2019. 4,5 Gastric cancer is a heterogeneous disease, with significant differences in pathological features, biological behaviours and gene expression profiles. Despite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 56 publications
0
38
0
Order By: Relevance
“…Plasma membrane transporters secure import of a wide range of substrates into the cytoplasm. Consistently, increased expression of several transporting proteins has been correlated to the increased metabolic activity of cancer cells and poor disease prognosis (Natecz, 2020 ; Sampedro-Núñez et al, 2020 ; Xu et al, 2020 ; Yamada et al, 2020 ).…”
Section: Introductionmentioning
confidence: 91%
“…Plasma membrane transporters secure import of a wide range of substrates into the cytoplasm. Consistently, increased expression of several transporting proteins has been correlated to the increased metabolic activity of cancer cells and poor disease prognosis (Natecz, 2020 ; Sampedro-Núñez et al, 2020 ; Xu et al, 2020 ; Yamada et al, 2020 ).…”
Section: Introductionmentioning
confidence: 91%
“…These amino acids serve as substrates in several biochemical and metabolic pathways in cancer cells. Previous studies have reported that the EAATs-mediated therapeutic resistance is related to altered tumor metabolic profiles (Ye et al, 1999;de Groot et al, 2005;Tao et al, 2011;Pedraz-Cuesta et al, 2015;Sun et al, 2019;Xu et al, 2020;Guo et al, 2021). It was found that the level of glutamate and aspartate increased in the radioresistant NPC cells compared to their parental cells (Figure 5A).…”
Section: Slc1a6 Up-regulated Glutamate Level and Drug Resistance Genesmentioning
confidence: 81%
“…Although the role of SLC1A6 in cancers was not well documented, other members of the SLC1A family were reported to be overexpressed in multiple tumors and predict poor prognosis. For example, expression of SLC1A1, SLC1A2 or SLC1A3 contributed to promoting tumor progression in solid tumors, such as lung cancer, glioma, and gastric cancer (Ye et al, 1999;de Groot et al, 2005;Tao et al, 2011;Xu et al, 2020;Guo et al, 2021). Besides, the SLC1A members were also reported to be associated with drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The PI3K/AKT signaling pathway serves an important role in regulating cell proliferation, migration and invasion ( 16 18 ). Therefore, in the present study, the western blotting assay was performed to determine whether circRNA_100395 function as a tumor inhibitor via regulating this signaling pathway.…”
Section: Resultsmentioning
confidence: 99%